TRANFORMASI DAN AKTUALISASI MAJELIS TARJIH DALAM PENDIDIKAN ISLAM DI SEKOLAH MUHAMMADIYAH - Yazida Ichsan; Unik Hanifah Salsabila; Difa'ul Husna (MUADDIB Jurnal Kependidikan dan Keislaman, 2022)
This article seeks to describe how the Tarjih Council transformed from time to time both in terms of decisions, manhaj, sources, techniques and approaches in historical perspectives and their actualization in Muhammadiyah education. Education itself is the most effective and strategic da'wah medium within Muhammadiyah so that the internalization and transmission of ideology, understanding and practicing religious teachings based on the Tarjih decision are absolute. The function of education within Muhammadiyah itself is inseparable from three things: integral scientific development, development of learning innovation and internalization of AIK in the social sphere. Research related to this theme is library research research. The approaches used are historical-analysis and philosophical. The results of the study indicate that in actualizing Tarjih products in Muhammadiyah education, three policy directions need to be applied, which include: first, planting tarjih and ta'did insights to educators and students. Second. Actualization of learning materials in accordance with the problems and challenges of changing times. Third, coaching educators in the AIK field as an effort to strengthen ideology and crystallization of values.